C-reactive protein to albumin ratio in atrial fibrillation - Abuş, Sabri (The European Research Journal, 2023)
Objectives: Atrial fibrillation (AF) may cause thromboembolism and cardiac morbidity and mortality. Patients with cardiovascular diseases are at risk for developing AF. In this study, the relationship between inflammation markers and AF was examined. Methods: Among 689 people followed up in the cardiology outpatient clinic for reasons such as hypertension, coronary artery disease, and rheumatic valve disease, 88 patients with AF and 601 patients without AF were compared. The blood parameters of the AF group were examined during the period when AF developed in the patients. Hemogram and biochemistry parameters of AF and non-AF groups were compared. Results: C-reactive protein to albumin ratio (CAR), neutrophil count to albumin ratio, neutrophil count to lymphocyte count ratio, and monocyte count to lymphocyte count ratio were significantly higher in the AF group than in the non-AF group (p < 0.001, p < 0.001, p = 0.001, and p < 0.001; respectively). According to the Receiver Operating Characteristics analysis, it was found that the CAR value of cut-off: 0.0533 could diagnose AF with 74% sensitivity (AUC: 0.789, CI 95%: 0.726-0.853, p < 0.001). Albumin value of cut-off: 3.75 was found to be able to diagnose AF with 82% specificity (AUC: 0.772, CI 95%: 0.707-0.836, p < 0.001). Conclusions: AF is an arrhythmia that should be recognized early due to the complications it causes, and the CAR value can be used in the diagnosis of AF in individuals with cardiac disease.